STORYTELLING THERAPY UNTUK LANSIA DENGAN DIMENSIA - Januardi; Ariyanti, Sri; Dwi Ariani, Desti (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Storytelling has been shown to improve mood, enhance cognitive function, and strengthen relationships among the elderly, their families, and caregivers. It also promotes social engagement and helps reduce feelings of loneliness. When combined with group interaction, storytelling therapy can increase self-confidence and encourage the elderly to express themselves more freely. Objective: This study aims to describe the application of storytelling therapy among elderly individuals with dementia at Graha Werdha Marie Joseph Pontianak. Methods: This quantitative study used a descriptive design. The sample consisted of 32 elderly participants selected through total sampling. Data were collected using structured observation and analyzed descriptively. Results: The findings showed that most participants were aged 60–74 years (24 respondents or 74.5%), and the majority were female (23 respondents or 71.9%). Most respondents had a low educational background (30 respondents or 93.7%). The implementation of storytelling therapy among the elderly at Graha Werdha Marie Joseph Pontianak was categorized as good, with 20 respondents (62.5%) demonstrating positive engagement. Regarding dementia level, the majority of the elderly (22 respondents or 68.8%) were classified as having mild or probable dementia. Conclusion: Most of the elderly at Graha Werdha Marie Joseph Pontianak are aged 60–74 years, predominantly female, and have low educational levels. The application of storytelling therapy is categorized as good and effectively supports elderly engagement. Most participants experience mild dementia, indicating storytelling therapy’s potential benefits in maintaining cognitive and emotional well-being.